2020
DOI: 10.22454/fammed.2020.785068
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of US Medical Schools to Primary Care (2003-2014): Determining and Predicting Who Really Goes Into Primary Care

Abstract: Background and Objectives: Schools of medicine in the United States may overstate the placement of their graduates in primary care. The purpose of this project was to determine the magnitude by which primary care output is overestimated by commonly used metrics and identify a more accurate method for predicting actual primary care output. Methods: We used a retrospective cohort study with a convenience sample of graduates from US medical schools granting the MD degree. We determined the actual practicing speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 8 publications
1
22
0
Order By: Relevance
“…Although a detailed discussion of these topics is beyond the scope of this description of our study, several strategies are well documented. First, medical schools must do better at admitting and supporting students who are interested in practicing rural Family Medicine 17,39,40,41 . Second, family medicine residencies must continue to provide training in care of both uncomplicated and complicated maternity care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a detailed discussion of these topics is beyond the scope of this description of our study, several strategies are well documented. First, medical schools must do better at admitting and supporting students who are interested in practicing rural Family Medicine 17,39,40,41 . Second, family medicine residencies must continue to provide training in care of both uncomplicated and complicated maternity care.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of United States medical school graduates entering Family Medicine has remained flat at around eight to ten percent for the last 15 years, 14 leading to calls for increasing that percentage to meet population needs and replace FPs who are retiring 15,16 . Compounding the issue, current metrics do not accurately predict the percentage of medical school graduates going into primary care, making workforce planning difficult 17 …”
Section: Introductionmentioning
confidence: 99%
“…This is known as the RMPCM. 3 However, because of the various subspecialty fellowships that residency graduates may enter after completion of their “first certificate” residency program, the RMPCM measurement magnifies the actual number of medical school graduates who eventually enter primary care practice at the conclusion of all their GME. For example, half of pediatrics residents and well over half of internal medicine residents enter subspecialty fellowships at the conclusion of their “first certificate” residency training.…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, Deutchman and colleagues proposed another method of GME output measurement by limiting the determination of a medical school’s primary care output to the match categories of family medicine, medicine-primary, pediatrics-primary, and medicine-pediatrics. 3 Deutchman and colleagues compared this method (IPPCM) to the traditional RMPCM, then used online resources to confirm the physicians’ actual practice specialty at the conclusion of their medical school, residency, and subspecialty fellowship training. Deutchman and colleagues concluded that the new “Intent to Practice Primary Care Method more accurately predicted a medical school’s actual primary care output than the Residency Match Primary Care Method”.…”
Section: Introductionmentioning
confidence: 99%
“…The requirement gap for general practitioners will still exist for a long time. In the future, it is necessary to implement the ‘Opinions’, increase the training of general medicine talents, and truly achieve the goal of ‘full coverage, complementing shortcomings, raising levels, and ensuring quality’ (Deutchman et al, 2020). A system objective described as a function of decision variables is referred to as an objective function in optimization.…”
Section: Introductionmentioning
confidence: 99%